Non-Standard Employment after Age 50: How Precarious Is It? - D’Amours, Martine (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2009)
Based on a qualitative study of the trajectories of 22 workers aged 50 or older who lost or left a standard job and then undertook some form of non-standard employment, this article wants to shed light on the quality of non-standard jobs often held by seniors. Can these jobs be categorized as precarious, and if so, what are the dimensions of this precariousness? Our analysis enabled us to identify three main profiles: early retirees, “competitive” non-standard workers, and vulnerable non-standard workers. This diversity is mainly related to the characteristics of the previous occupational trajectory but also to the characteristics of the repositioning job, the type of skills the worker has, gender, age, and the fact of living or not with a spouse.